Use of E-resources by Faculty Members and Students in Pokhara University - Dallakoti, Min Kumari (Access: An International Journal of Nepal Library Association, 2023)
Objectives: Online resources are widely used in universities but their use and types of resources may vary in different countries and universities across the globe. The study aims to find out the type of online resources accessed by faculties, members and students of constituent colleges of Pokhara University. Methodology: The study selected 80 samples among the faculty members and students of constituent colleges of Pokhara University using stratified, purposive, and quota sampling methods. Opinion was collected through a structured questionnaire and data were analyzed with descriptive statistics. Conclusion: The intentions of the use of online resources are mostly to search the articles, books, theses, indexing and abstract which is used for writing articles and books, theses, project works and term papers, preparing materials for the training, seminars, and conferences and also preferred to update knowledge. Large number of respondents spent an average of three hours getting and study of online resources. Almost half of the online resource users have already published some works that indicates online resources are instrumental to enhance the academic excellence and knowledge generation. Practical implications: However, the student got oriented about library resources before their class started; still, there is somehow a lack of information-searching skills. The study provides input to university authorities to improve the existing online resources facilities and gives insight into the users’ behaviors.